Peran Program Keluarga Harapan Terhadap Peningkatan Ekonomi Keluarga Penerima Manfaat (KPM) Di Kecamatan Banjarmasin Timur Kota Banjarmasin - Yunia, Elvera; Wardhana, Ali (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to determine the implementation and role of the Family of Hope program in improving the KPM economy in the East Banjarmasin District, Banjarmasin City. The type of research used is descriptive qualitative, with a research sample of 96 KPM. This study shows that the Implementation of the Family Hope Program in East Banjarmasin District has been going very well, seen from the active role of facilitators who regularly hold meetings with KPM and a change in KPM's mindset and the amount of assistance is appropriate without any deductions. Then, the most dominant role of the Family of Hope program is found in the income indicator, which is around 76%. Changes in KPM's mindset in controlling the funds provided have helped KPM meet their daily needs and others, increasing household spending above the poverty line. This indicates an increase in the KPM household economy.